Satisfaction with nursing care among past-operative charity patients in surgical words in tertiary hospital in the Philippines - Agravante, Ma. Genia Theresa T.; Aguirre, Ayra Jhoana G.; Banayat, Aprille C.; Buendia, Maria Jill M.; Daya, Mari Francine Krizia B.; Deoso, Regina Gaile G.; Manahan, Jierah R.; Quiat, Joan Leslie A.; Raymundo, Andre P.; Salonga, Raymond D.; San Juan, Ingrid B.; Temporal, Nicolai Ivan M.
Background. Patient satisfaction, now considered an important patient outcome, a good predictor of patient compliance, and an adequate measure of the quality of health services, is recognized by nurses as a route towards improving nursing care. The researchers also aligned themselves with the goal of the target tertiary hospital towards certification by the International Organization for Standardization, which highlights the desirability of patient satisfaction.